House Of Quality (Hoq) Approach To Women's Backpack Design Using Quality Function Deployment (Qfd) Method - Taptajani, Dedi Sa’dudin; Mubarok, Muhammad Syauqi; Aziz, Ripki Abdul; Hamidah, Ucu Siti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The need for backpacks is increasing along with increased mobility, including among women. Backpacks are needed by women who do a lot of activities and have to carry lots of things to support their daily activities, be it school, college, or work. With so many choices of backpacks available in the market, it is not uncommon for many women to be confused about choosing a backpack that suits their needs. Therefore, it is necessary to conduct a study to help formulate the characteristics of an ideal backpack for students, university students, and women in general who often carry a lot of things to support their various daily activities. Using the Quality Function Deployment Method or House of Quality approach, the authors try to find a formula for the design characteristics of backpacks that are expected by consumers in the market, especially students, female students and women in general who have high mobility. The characteristics used as a reference will be based on the seven dimensions of product quality. Expectations and wishes of consumers regarding the characteristics of an ideal backpack will be contained in an opinion poll which is then formulated using the QFD or HOQ methods. The result of the analysis of this research is to know the characteristics of an ideal backpack to support the activities of students, female students and women who have high mobility.